Autophagy of cytoplasmic bulk cargo does not require LC3. Issue 2 (1st February 2016) - Engedal, Nikolai; Seglen, Per O.
ABSTRACT: To investigate the role of LC3 in bulk autophagy we compared its autophagic-lysosomal processing (using an improved quantitative immunoblotting method) with autophagic-lysosomal bulk cargo flux (measured by our established LDH [lactate dehydrogenase] sequestration assay) in amino acid-starved rat hepatocytes treated with cycloheximide to prevent new LC3 influx. Block-release experiments with the reversible autophagy inhibitors 3-methyladenine (3MA) and thapsigargin (TG) showed that while only 3MA suppressed phagophoric LC3 attachment (lipidation), both inhibitors prevented phagophore closure (cargo sequestration). Upon release from closure blockade, some autophagic-lysosomal LC3 flux was resumed even in the presence of 3MA, i.e., without an accompanying bulk cargo flux. Conversely, whereas the autophagic-lysosomal flux of LC3 halted within ∼100 min of cycloheximide treatment, the bulk cargo flux continued at a high rate. siRNA-mediated knockdown of LC3 family proteins in LNCaP prostate carcinoma cells confirmed that autophagy of cytoplasmic bulk cargo was completely LC3 independent also in these cells, and in the absence of cycloheximide. However, a strong requirement for GABARAP family proteins was evident. Since bulk autophagy of cytoplasm (macroautophagy) and autophagic-lysosomal LC3 processing may apparently be mutually independent, LC3 would seem to be unsuitable as a general indicator of autophagy.